ASSESSING THE RISK FACTORS AND COMPLICATIONS RELATED TO METABOLIC SYNDROME IN DIABETIC PATIENTS: A RETROSPECTIVE ANALYSIS FROM METABESITY MANAGEMENT CLINICS. - Mujtaba Hasan; Sadia Salman; S. Abbas Raza; Fawad Ahmad Randhawa; Muhammad Asim Rana (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: This study aimed to assess the risk factors and complications related to Metabolic Syndrome in Type 2 Diabetes Mellitus (T2DM) patients presented at the Metabesity Management Clinics.Methods: A retrospective cross-sectional study was conducted at two tertiary care centers over two years, including type 2 diabetic patients aged 18 and above. Patients with specific conditions or critical illnesses were excluded. Data, encompassing medical history, demographics, and various clinical measurements, were collected from medical records using Healthwire software.Results: The analysis revealed hypertension (53.3%) as the predominant risk factor associated with MetS among T2DM patients. Furthermore, Diabetic Peripheral Neuropathy (40.0%) emerged as the most prevalent microvascular complication in this population. Lower extremity vascular health, assessed by DFA-TBPI (0.80 ± 0.19), demonstrated consistent results, while DFA-ABPI (1.06 ± 0.06) indicated stable blood flow. Neurological assessments revealed moderate sensory perception in both right (12.15) and left (12.97) feet, with notable variability. A significant proportion (33.2%) reported mild depression based on PHQ-9 outcomes. The categorical distribution based on the FIB-4 score indicated a high level in 1.0% of respondents, with 15.9% at an intermediate stage. Conversely, the NFS score demonstrated that 0.1% exhibited high fibrosis advancement, while 53.4% were at an intermediate level.Conclusion: Hypertension was identified as the most prevalent risk factor and peripheral neuropathy as the most common microvascular complications associated with MetS among type 2 diabetes patients.